KOLABORASI JARINGAN PELAYANAN PUBLIK DALAM PENCEGAHAN DAN PENURUNAN STUNTING DI WILAYAH KABUPATEN BUTON TENGAH - Mursalim; Adrian Tawai; Rulinawaty (Halu Oleo University, 2025)
This study aims to analyse the forms of public service network collaboration in efforts to prevent and reduce stunting in Buton Tengah Regency. Using a descriptive qualitative approach, data were collected through in-depth interviews, observation, and documentation involving various actors such as government institutions, health workers, communities, and the private sector. The findings reveal that stunting is a complex issue requiring a cross-sectoral approach, engaging actors with diverse but complementary roles and responsibilities. An ideal collaboration model demands shared commitment, evidence-based data utilisation, structured communication, and increased human resource capacity. Implementation barriers include weak coordination, complex bureaucratic procedures, and low public health literacy. Therefore, strengthening collaborative governance, inclusive policy support, and sustainable participatory monitoring and evaluation are essential. This study recommends enhancing stakeholder synergy and increasing community involvement as key strategies for significantly reducing stunting prevalence in the region.